Transforming Islamic Moral Education: Applying Problem-Based Learning to Address Youth Socioreligious Issues - Siti Ma'rifah; Moh. Irmawan Jauhari; Ahmad Khoirul Mustamir Mustamir; Fadhil Akbar; Aji Wahyudin (Al-Qalam Institue, 2026)
This study examines how Problem-Based Learning (PBL) in Islamic Religious Education (IRE) addresses adolescents’ socioreligious challenges. Indonesian Muslim students navigate digital misconduct, peer problems, and cultural tensions requiring moral judgment. Conventional text-centered instruction may provide normative knowledge without developing ethical reasoning, social responsibility, or religious resilience. A qualitative case study was conducted at a pesantren-based high school in East Java, Indonesia. Data were collected through interviews, classroom observations, focus groups, and document analysis, thematically analyzed through condensation, display, and verification. First, PBL shifted students from memorizing religious texts toward contextual digital ethical reasoning. Students applied tabayyun and responsible speech to hoaxes, cyberbullying, online gambling, and social-media behavior. Second, PBL broadened piety from ritual observance toward empathy, inclusion, peer support, and environmental responsibility. Students interpreted ukhuwah Islamiyah as an obligation for care. Third, PBL created a safe space for discussing identity, popular culture, and relationships. Facilitated dialogue helped students resolve religious dissonance without abandoning Islamic principles. The study contributes a contextual-dialogic model integrating ethical reasoning, social piety, and religious resilience. Practically, it supports case-based curricula, facilitative teacher development, and student support.